The Role of STAF-Based Digital Transformation in Enhancing Financial Inclusion in Islamic Rural Banks in Indonesia - Syahruddin Yasen; Halihasimi Halihasimi; Endy Muhammad Astiwara (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid development of digital technology has created both opportunities and challenges for Islamic financial institutions in expanding financial inclusion. This study examines the role of STAF-based (Shiddiq, Tabligh, Amanah, and Fathanah) digital transformation in enhancing financial inclusion within Islamic Rural Banks (Bank Pembiayaan Rakyat Syariah/BPRS) in Indonesia. The research employs a library research approach by reviewing relevant books, scientific journals, institutional reports, and previous studies related to digital transformation, Islamic financial inclusion, and Islamic banking. Data were analyzed using content analysis to identify patterns, relationships, and key insights concerning the integration of Islamic ethical values into digital transformation initiatives. The findings indicate that digital transformation contributes significantly to expanding access to financial services, improving operational efficiency, and reaching underserved communities. Furthermore, incorporating STAF values strengthens transparency, communication, accountability, innovation, and customer trust, which are essential to promoting financial inclusion. The study concludes that STAF-based digital transformation provides a value-driven framework that aligns technological advancement with Islamic ethical principles, thereby supporting the sustainable development of BPRS and fostering inclusive financial growth in Indonesia.